(untitled) (Research, Society and Development, 2022)
The great demand on the part of professionals and patients for aesthetic dental restorations has led to great evolutions in the composition of composite resins. Some composites have excellent mechanical and optical properties, mimicking important characteristics of the dental element very naturally. However, making excellent composite resin restorations is not just about choosing which resin to use in each case. It is extremely important that all the necessary procedures are carried out for the preparation and correct completion of resin restorations. Among these are the finishing and polishing steps which are important for the esthetics, longevity of the restoration and the patient’s periodontal health. However, this step is neglected by some professionals. This work aims to describe the advantages and disadvantages of composite resins available on the market and demonstrate the importance of finishing and polishing in composite resin restorations, presenting some of the options available today in the current market. A descriptive narrative literature review was carried out on the proposed theme, using as a bibliographic basis scientific articles published between 2003 and 2021, available in the online databases BVSalud, PubMed, Scielo, Lilac and Google Scholar, available in the languages Portuguese and English. At the end of this work, it was concluded that it is extremely important that dentists become aware of the importance of carrying out finishing and polishing procedures to improve the quality of their direct restorations in composite resins.